ÐšÐ¾Ñ€Ñ€ÐµÐºÑ†Ð¸Ñ Ð¿Ñ€ÐµÐ¿Ð°Ñ€Ð°Ñ‚Ð¾Ð¼ ÐºÐ¾Ñ€Ð´Ð¾Ð²Ð¾Ð¹ ÐºÑ€Ð¾Ð²Ð¸ "ÐšÑ€Ð¸Ð¾Ñ†ÐµÐ»Ð»-Ð“ÐµÐ¼Ð¾ÐºÐ¾Ñ€Ð´" Ð¼ÐµÑ‚Ð°Ð±Ð¾Ð»Ð¸Ñ‡ÐµÑÐºÐ¸Ñ… Ð½Ð°Ñ€ÑƒÑˆÐµÐ½Ð¸Ð¹ Ð¿Ñ€Ð¸ Ð¾ÑÑ‚Ñ€Ð¾Ð¼ Ð³Ð½Ð¾Ð¹Ð½Ð¾Ð¼ Ð¿ÐµÑ€Ð¸Ñ‚Ð¾Ð½Ð¸Ñ‚Ðµ - Goltsev, K. A.; Ovsyannikov, S. Ye.; Kozhina, O. Yu.; Ostankov, M. V.; Goltsev, A. N. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2011)
The method of correction of metabolic impairments with "Cryocell-Hemocord" cord blood preparation in experimental model in rats with an acute purulent peritonitis was tested. It has been shown that its application with antibiotics as a combined treatment of this pathology contributed to the correction of impairments of free radical oxidation, lessening of hypoxia rate, improvement of oxygen utilization by the tissues, survived hypoxia, recovery of antioxidant protection systems.